Contrast of a knowledge management model in a public university in central Mexico - García Lirios, Cruz (2019)
Often, knowledge-generating organizations have been studied from the influence of their culture, structure and flexible and innovative processes, or from the influence of their leadership and the continuous training of their talents. In the present work, a higher education institution was well researched from the topics established in the specialized literature from 2010 to 2018, the discourses of key informants and the reliability as well as the validity of an instrument that measured its underlying factors. For this purpose, three investigations were carried out: One documentary, another qualitative and another correlational in order to specify a model for the study of the phenomenon in question. The results show a prevalence of knowledge generation as a second order construct and a representation of its dimensions around the categories of «alliances», «networks» and «climates», as well as a factorial structure around the motivation, innovation and communication of opportunities based on resources and capabilities. Lines concerning empathy, commitment and satisfaction are seen as factors that would increase the percentage of the total variance explained, which was 54%.